Identificación del Burnout en una muestra de médicos/as y enfermeros/as durante el año 2017 - Acurio Gallo, Juan Pablo (2018)
ABSTRACK: The main objective of this research was to identify the burnout syndrome in its three dimensions (emotional exhaustion, depersonalization and personal fulfillment) in a sample of 20 doctors and nurses. Regarding the methodological process, it was a quantitative research, not experimental, transactional, descriptive and exploratory; the sample was non-probabilistic and accidental accessibility. The data were collected with the application of the following instruments: questionnaire of sociodemographic and labor variables ad-hoc, MBI, GHQ-28, BRIEF-COPE-28, MOS and EPQR-A. The data obtained in these public and private medical facilities in the country determined that there is no Burnout Syndrome in the sample investigated, because the scores of emotional exhaustion are: doctors / as 46.2; nurses 46.2%; and medical depersonalization 38.5%; nurses / as 42.9%, as well as personal fulfillment are: doctors / as 42.9% and nurses 28.6%; These values are optimal and help to avoid burnout syndrome.